ANALISIS KELAYAKAN FINANSIAL PENGEMBANGAN USAHA BUDIDAYA JAMUR TIRAM : (Studi Kasus Pada Perusahaan Bale Jamur di Desa Adimulya Kecamatan Wanareja Kabupaten Cilacap) - Kirani , Andri Hayu (Profit : Jurnal Inovasi Ekonomi dan Bisnis, 2023)
This study aims to analyze the financial feasibility of the Bale Mushroom cultivation business in Adimulya Village, Wanareja District, Cilacap Regency. The primary method used in this research is the descriptive method. The determination of respondents was done purposively (purposive). The types and sources of data used are primary through direct interviews with business owners and secondary data obtained through journals and theses. The data analysis includes the Revenue Ratio over Total Cost, Net Present Value, Payback Period, and Break Event Point. The study's results were: 1) the value of the R/C ratio was 1.9. 2) The NPV of the BI interest rate is 5.75%, IDR 26,464,458. 3) The required PP is for five months and four days. Moreover, 4) the production BEP is 77.26 kg, and the price BEP is IDR 13,386. From these four data analyses, the results are feasible so that the oyster mushroom business in the Bale Mushroom business is financially feasible to develop.